2016
DOI: 10.1371/journal.pone.0145049
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid Hormone Activates Brown Adipose Tissue and Increases Non-Shivering Thermogenesis - A Cohort Study in a Group of Thyroid Carcinoma Patients

Abstract: Background/ObjectivesThyroid hormone receptors are present on brown adipose tissue (BAT), indicating a role for thyroid hormone in the regulation of BAT activation. The objective of this study was to examine the effect of thyroid hormone withdrawal followed by thyroid hormone in TSH-suppressive dosages, on energy expenditure and brown adipose tissue activity.Subjects/MethodsThis study was a longitudinal study in an academic center, with a follow-up period of 6 months. Ten patients with well-differentiated thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 40 publications
6
44
1
1
Order By: Relevance
“…In rodents, TH act directly at nuclear thyroid hormone receptors located in brown adipocytes to transcriptionally upregulate UCP1 expression (Weiner et al 2017). Furthermore, clinical data demonstrate that BAT activity is higher in the subclinical hyperthyroid state than in the hypothyroid state (Broeders et al 2016), supporting the notion that endogenous TH regulate BAT thermogenesis. Although the classical action of T3 is thought to be peripherally mediated, more recent studies have shown that TH can also act centrally within the hypothalamus to regulate BAT thermogenesis.…”
Section: Neuroendocrine Control Of Energy Balancementioning
confidence: 81%
“…In rodents, TH act directly at nuclear thyroid hormone receptors located in brown adipocytes to transcriptionally upregulate UCP1 expression (Weiner et al 2017). Furthermore, clinical data demonstrate that BAT activity is higher in the subclinical hyperthyroid state than in the hypothyroid state (Broeders et al 2016), supporting the notion that endogenous TH regulate BAT thermogenesis. Although the classical action of T3 is thought to be peripherally mediated, more recent studies have shown that TH can also act centrally within the hypothalamus to regulate BAT thermogenesis.…”
Section: Neuroendocrine Control Of Energy Balancementioning
confidence: 81%
“…In a recent human study, Cypess et al show that a β3-adrenergic receptor agonist can activate BAT [58]. Broaeders et al report that levothyroxine treatment improves human BAT activation in response to cold [35]. Thyromimetics that specifically target BAT may be useful for pharmacological activation of BAT [39] while potentially have less side effects than TH.…”
Section: Resultsmentioning
confidence: 99%
“…Thyroid hormone activates non-shivering thermogenesis by increasing metabolic activity in BAT. Hypothyroid patients have decreased adaptive thermogenesis during cold exposure that is corrected by thyroid hormone replacement [35] whereas hyperthyroid patients can undergo activation of thermogenesis, even at room temperature [36]. During cold exposure, sympathetic stimulation of BAT increases DIO2 expression and raises intracellular T 3 concentration [5,37].…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have investigated the effects of circulating thyroid hormones on human BAT, the results have been contradictory. Thyroidectomized patients subjected to 18 F-FDG PET/CT imaging after cold exposure, both in a hypothyroid state (high TSH, low FT4) and during a thyrotoxic state (suppressed TSH, high FT4), showed significantly higher BAT activation during thyrotoxicosis (29). Nine patients with Graves' hyperthyroidism underwent 18 F-FDG PET/CT imaging at room temperature both during hyperthyroidism (suppressed TSH, high FT4) and euthyroidism (normal TSH, normal FT4).…”
Section: Discussionmentioning
confidence: 99%